Case Report: A Novel Missense Variant in the SIPA1L3 Gene Associated With Cataracts in a Chinese Family - Yang, Duo; Zhou, Haiyan; Lin, Jiwu; Zhao, Shuangxi; Zhou, Hao; Yin, Zhaochu; Ni, Bin; Chen, Yong; Xie, Wanqin (Frontiers in Genetics, 2021)
The signal-induced proliferation-associated 1-like 3 (SIPA1L3) gene that encodes a putative Rap GTPase-activating protein (RapGAP) has been associated with congenital cataract and eye development abnormalities. However, our current understanding of the mutation spectrum of SIPA1L3 associated with eye defects is limited. By using whole-exome sequencing plus Sanger sequencing validation, we identified a novel heterozygous c.1871A > G (p.Lys624Arg) variation within the predicted RapGAP domain of SIPA1L3 in the proband with isolated juvenile-onset cataracts from a three-generation Chinese family. In this family, the proband's father and grandmother were also heterozygous for the c.1871A > G variation and affected by cataracts varying in morphology, severity, and age of onset. Sequence alignment shows that the Lys 624 residue of SIPA1L3 is conserved across the species. Based on the resolved structure of Rap1–Rap1GAP complex, homology modeling implies that the Lys 624 residue is structurally homologous to the Lys 194 of Rap1GAP, a highly conserved lysine residue that is involved in the interface between Rap1 and Rap1GAP and critical for the affinity to Rap·GTP. We reasoned that arginine substitution of lysine 624 might have an impact on the SIPA1L3-Rap·GTP interaction, thereby affecting the regulatory function of SIPA1L3 on Rap signaling. Collectively, our finding expands the mutation spectrum of SIPA1L3 and provides new clues to the molecular mechanisms of SIPA1L3-related cataracts. Further investigations are warranted to validate the functional alteration of the p.Lys624Arg variant of SIPA1L3.